2017
DOI: 10.1073/pnas.1707531114
|View full text |Cite
|
Sign up to set email alerts
|

MLKL forms disulfide bond-dependent amyloid-like polymers to induce necroptosis

Abstract: Mixed-lineage kinase domain-like protein (MLKL) is essential for TNF-α-induced necroptosis. How MLKL promotes cell death is still under debate. Here we report that MLKL forms SDS-resistant, disulfide bond-dependent polymers during necroptosis in both human and mouse cells. MLKL polymers are independent of receptor-interacting protein kinase 1 and 3 (RIPK1/RIPK3) fibers. Large MLKL polymers are more than 2 million Da and are resistant to proteinase K digestion. MLKL polymers are fibers 5 nm in diameter under el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(138 citation statements)
references
References 46 publications
9
123
0
Order By: Relevance
“…MLKL finally forms oligomers and incites binding of the NTD to the plasma membrane [61]. The phosphorylation-dependent oligomerization of MLKL starts from forming tetramers which serves as building blocks for larger polymers [62]. It has been reported that MLKL forms an octamer through two tetramers with disulphide bonds at α-helices 4 and 5 within the KLD [63].…”
Section: Mlkl Is the Effector Protein In Necroptosismentioning
confidence: 99%
“…MLKL finally forms oligomers and incites binding of the NTD to the plasma membrane [61]. The phosphorylation-dependent oligomerization of MLKL starts from forming tetramers which serves as building blocks for larger polymers [62]. It has been reported that MLKL forms an octamer through two tetramers with disulphide bonds at α-helices 4 and 5 within the KLD [63].…”
Section: Mlkl Is the Effector Protein In Necroptosismentioning
confidence: 99%
“…With this evidence, it was concluded that MLKL was not dissociating from the fibers during the SDD-AGE process and that the MLKL-containing fibers seen in Figure 1 were indeed distinct from the RIPK1/RIPK3 fibers. Furthermore, when RIPK3 was immuno-depleted from the cell lysates, the MLKL fibers remained intact 4 , confirming that MLKL fibers and RIPK1/RIPK3 fibers are indeed distinct entities.…”
Section: Representative Resultsmentioning
confidence: 72%
“…More recently, the formation of amyloid or amyloid-like fibers has been shown to be a part of signaling pathways in humans, including during anti-viral innate immune response 2 and necroptosis 3,4 , and in lower organisms such as yeast 5,6 . Therefore, the ability to detect these fibers in the lab is important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two inhibitors were employed to determine whether the stimulated death pathway was canonical MLKL-and RIP3-dependent necroptosis. GSK'872 binds to and inhibits the RIP3 kinase domain (31,32), whereas necrosulfonamide (NSA) inhibits downstream effector functions of MLKL via covalent reaction with the Cys86 residue of human but not murine MLKL (17,33). NSA and GSK'872 inhibited TBZ-induced cytotoxicity in HFFF-TERTs, indicating that these cells expressed sufficient RIP3 to induce measurable canonical necroptosis ( Figure 3C).…”
Section: Pul36 Protects Cells From Necroptosismentioning
confidence: 99%